The performance of intravoxel-incoherent motion diffusion-weighted imaging derived hypoxia for the risk stratification of prostate cancer in peripheral zone. Issue 125 (April 2020) - Chen, Zhongwei; Xue, Yingnan; Zhang, Zhao; Li, Weikang; Wen, Min; Zhao, Youfan; Li, Jiance; Weng, Zhiliang; Ye, Qiong
Highlights: IVIM derived hypoxia parameters correlate with aggressiveness of PCa. IVIM derived hypoxia could provide a noninvasive and visual method to detect intratumoral hypoxia. IVIM derived hypoxia may contribute to the risk stratification of PCa in PZ. Abstract: Purpose: To assess the association between intravoxel-incoherent motion diffusion-weighted imaging (IVIM) derived hypoxia and the aggressiveness of prostate cancer (PCa) and to explore its contribution to the risk stratification of PCa. Methods: Seventy-five peripheral zone (PZ) PCa patients, who underwent multiparametric MRI (mpMRI), were included in this study. Systematic ultrasound guided biopsy was used as reference. IVIM was acquired with 5 b values (b = 0∼750 s/mm 2 ). Apparent diffusion coefficient (ADC), pure tissue diffusion (Ds), volume fraction of pseudo-diffusion (fp), hypoxic fraction (HFDWI ), hypoxia score (HSDWI ) and relative oxygen saturation(rOSDWI ), were calculated and histogram analysis was applied. Groups comparison was performed between low-intermediate-grade group (LG, the International Society of Urological Pathology (ISUP) Gleason Grade (GG) ≤2) and high-grade (HG, ISUP GG ≥ 3) group. The correlation between diffusion parameters and ISUP GG was assessed. Cross-validated Support Vector Machine (SVM) Classification was performed and compared with univariate ROC analysis to explore the risk stratification of PZ PCa. Results: Mean, median, and the 10th percentile of Ds differed significantly between groups ( p < 0.05). Several parameters significantly correlated with ISUP grade, and the 10th percentile of Ds showed the strongest correlation (ρ= − 0.284). The prediction model containing IVIM derived hypoxia yielded an area under the receiver operating characteristics curve (AUC) ranging 0.749–0.786 for cross-validation. The AUCs of the SVM modeling were higher than that of any single parameter. Conclusion: IVIM derived hypoxia demonstrated significant correlation with the aggressiveness of PCa. It's supplemental to the MRI assessment of PCa with a promising stratification of risk stratification of PZ PCa.